2016
DOI: 10.1080/24748668.2016.11868945
|View full text |Cite
|
Sign up to set email alerts
|

Elite football player engagement with performance analysis

Abstract: Abstract:Despite the wide spread employment of Performance Analysis (PA) within the football coaching process to enhance augmented feedback, until recently little consideration has been given to the context in which PA delivery takes place at elite levels and subsequently impacts on players receiving such information. The aim of this investigation was to explore players' preferred engagement with the PA approach. Comparisons were also drawn between Senior and Academy players. Method: A two phase methodology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
0
27
1
4
Order By: Relevance
“…The interview was completed in a one-to-one format (participant and interviewer) lasting 85 AE 15 min and recorded via Dictaphone in a similar manner to Wright et al 28 and Francis and Jones. 25 Interviews were transcribed within Express Scribe (NCH Swift Sound) and then offered back to each participant to verify response accuracy and provide additional information where appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interview was completed in a one-to-one format (participant and interviewer) lasting 85 AE 15 min and recorded via Dictaphone in a similar manner to Wright et al 28 and Francis and Jones. 25 Interviews were transcribed within Express Scribe (NCH Swift Sound) and then offered back to each participant to verify response accuracy and provide additional information where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Mooney et al, 29 about three-quarters of participants provided video/data post-performance frequently, with > 86% suggesting that increasing this would be beneficial to learning, although this mainly affirms their belief in their role. Francis and Jones 25 and Wright et al 28 also suggested the use of video and data supports individual reflection and enables a deeper understanding of performance through a more holistic view. Moreover, increasing feedback, either directly (coach input) or indirectly (individual reflection), may create greater opportunity to impact development.…”
Section: Feedback Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…O’Donoghue (2010) showcased that performance analysis has become a validated support structure for coaches and athletes and although there is a body of research which investigates the role of the analyst (Bampouras et al, 2012; Wright et al, 2013) and the perceptions of performance analysis within the coaching process (Francis and Jones, 2014; Wright et al, 2016), there is a scarcity of information surrounding the way coaches create, interact and maintain working relationships with performance analysts (Wright et al, 2013). The relationship between the analyst and coach has however, been shown to be so important that coaches would attempt to recruit analysts that they have worked with in previous roles when they gain new employment (Reid et al, 2004; Butterworth and Turner, 2014; Huggan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%